Sliding Friction of Steel Combinations - Nuruzzaman, D. M.; Chowdhury, M. A.; Kowser, M. A.; M. M., Rahman; Roy, B. K.; Chakraborty, S.; Islam, M. D.; Aktaruzzaman, M.; Mohammad, N. (Bentham Science Publishers, 2014)
Tribological characteristics of steel combinations are observed in this study using rotating tribometer. Experiments are done under different roughnesses of pin slides on stainless steel disc for different operating conditions. Certain trends are obtained between friction and rubbing durations. During experiment, it is found that there are significant relationship between friction coefficient and operating parameters. In fact, at initial stage friction coefficients of tested material are increased at a particular level with time and finally the friction becomes steady for remaining investigation period. Studies indicate that lower values of friction are obtained with higher loads for SS 202 slides against different roughnesses of mild steel counterface. Under similar conditions, higher values of frictions are found with higher values of sliding velocity. In addition to that, wear rates show higher values with higher load and velocity conditions. Tribological characteristics are varied for different roughnesses of pin materials under experimental ranges of two influencing parameters.